The Relationship between Sleep Hygiene and Adolescent Sleep Quality in the Dangdeur Subang Area - Dika Andriana; Angga Kusuma, M. Iqbal; Ratna Palupi, Eva Riantika; Handayani, Fitri; Primasari, Nessy Anggun (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Adolescence is a critical period in physical and psychological development that requires optimal sleep quality. Poor sleep hygiene can negatively impact the quality of adolescent sleep, especially for those who live in boarding houses and are far from parental supervision. Objective: This study aims to determine the relationship between sleep hygiene and adolescent sleep quality in Dangdeur Subang Village. Methods: The research design used was quantitative with a cross-sectional approach. The sample consisted of boarding school teenagers who were selected through a simple random sampling technique. The instruments used were the Sleep hygiene Index (SHI) questionnaire and the Pittsburgh Sleep Quality Index (PSQI). Data analysis was carried out using the spearman rank correlation test. Results and Discussion: The results of the study showed that the majority of adolescents had poor sleep hygiene behavior and poor sleep quality. There was a significant association between sleep hygiene and sleep quality (p < 0.05), suggesting that adolescents with good sleep hygiene tended to have better sleep quality. Conclusion: This study emphasizes the importance of education and behavioral intervention of sleep hygiene in adolescents, especially those living in boarding school environments. It is hoped that the results of this study can be the basis for a more effective sleep health promotion program for adolescents.